Translocator protein: pharmacology and steroidogenesis. (3rd August 2015) - Midzak, Andrew; Zirkin, Barry; Papadopoulos, Vassilios
Abstract : The translocator protein (TSPO; 18k Da) is an evolutionarily conserved outer mitochondrial membrane (OMM) protein highly expressed in steroid-synthesizing cells and found to possess a number of physiological and drug-binding partners. Extensive pharmacological, biochemical and cell biological research over the years has led to a model of TSPO involvement in mitochondrial cholesterol transport and promotion of steroid synthesis, a model guiding the design of drugs useful in stimulating neurosteroid synthesis and alleviating psychopathological symptoms. The involvement of TSPO in these processes has been called into question; however, with the publication of TSPO-deletion mouse models which saw no changes in steroid production. Here, we review work characterizing TSPO in steroidogenesis and offer perspective to research into TSPO pharmacology and its involvement in steroid biosynthesis.